A transdisciplinary explanatory critique of environmental education - Price, Leigh (Rhodes University, Faculty of Education, Department of Education, 2007)
This study originates out of my experience as an environmental educator working within business and industry in Zimbabwe and South Africa. It is motivated by my observation that, despite much environmental rhetoric and training, environmental education in industry rarely leads to significant advances towards environmental protection. I assume that the problem of the mismatch between rhetoric and action involves both semiotic and non-semiotic components and therefore, after a thorough exploration of my methodological options, I adopt a qualitative transdisciplinary textual analysis of relevant documents using Fairclough's Critical Discourse Analysis and Bhaskar's Dialectical Critical Realism, with some insights taken from Bhaskar's more recent concept of Meta-Reality. My main conclusions from the study indicate that causally efficacious philosophical mistakes, relating to theories of structure/agency and theories of epistemology, are an important aspect of the problem being considered. Specifically, I demonstrate that these mistakes function to buttress ideology and its attendant contradictions which in turn function to provide the preconditions that maintain inequalities and poor environmental practice in business and industry. Prior and current events, such as climate change and the trend towards globalisation, the 'free market economy' and psychological characteristics of the author, relevant to the problem, are also important. In line with Bhaskar's emancipatory aim for explanatory critique, I end with tentative recommendations for a re-imagined environmental education for business and industry which require (un)action. Consistent with my methodological choices, my recommendations have a (qualified) universal application, despite my focus on texts from South Africa and Zimbabwe. My recommendations are summarised below: "¢ there should be consistency between theory and practice such that performance contradictions are avoided; "¢ we should not act from a fear of survival based on past, no longer relevant experiences (e.g. from childhood) as this is unlikely to be an adequate base for present actions; "¢ we should avoid voluntarism by acting with the resources at our disposal, based on a true understanding of our strengths and weaknesses and our own specificities; "¢ we should avoid assuming the stance of the 'victim' by refusing to blame other agents or circumstances, without distorting or underestimating the causal efficacy of those agents or circumstances (related to avoiding voluntarism, whilst nevertheless not resorting to determinism either); "¢ we should direct our action towards the abolition of inequalities and master-slave relationships (related to the avoidance of performance contradictions); "¢ we should act from the position of epistemological humility, rather than from the position of epistemological privilege; "¢ we should consider action as 'shedding' based on an understanding of the Transformational Model of Social Activity (TMSA); and "¢ we should consider learning to be 'shedding' based on the necessity of (un)knowledge, or ignorance, as a requirement of arriving at relatively new knowledge. This study is also a contribution to contemporary methodological discussions relevant to Critical Discourse Analysis in that it extends these discussions to include psychoanalytical (as well as the more familiar phenomenological and ideological) depth explanations of lived illusion. Furthermore, this study is an experimental attempt to apply the concept of 'meta-reflexivity' in Critical Discourse Analysis.
Keywords: Environmental education; Business enterprises -- Environmental aspects; Corporations -- Environmental aspects; Social responsibility of business; Social responsibility of business -- Study and teaching; Environmental education -- Philosophy; Environmental ethics -- Study and teaching